Cardiovascular responses induced in free-moving rats by immune cytokines. - Morimoto, K (1992)
1. We investigated the effect of intraperitoneal (I.P.) injections of the immune cytokines, interleukin-1 beta (IL-1 beta) and tumour necrosis factor (TNF) on cardiovascular responses in free-moving rats, using a biotelemetry system. 2. The I.P. injection of a small dose of IL-1 beta (1 microgram/kg) induced a monophasic increase in the heart rate, and that of a large dose (10 micrograms/kg) induced biphasic increases in the blood pressure and heart rate. However, the I.P. injection of any of several doses of TNF (1, 10 and 50 micrograms/kg) had no effect on cardiovascular responses in rats. 3. Pre-treatment with I.P. injection of indomethacin (10 mg/kg), an inhibitor of cyclo-oxygenase, significantly suppressed the cardiovascular responses and the increase in the plasma noradrenaline (NA) concentration induced by I.P. injection of IL-1 beta. 4. Microinjection of IL-1 beta (1 and 10 ng) into the preoptic and anterior hypothalamic (PO-AH) region induced dose-dependent increases in the blood pressure and heart rate in rats. These responses were also suppressed by pretreatment with I.P. indomethacin (10 mg/kg). In addition, microinjection of prostaglandin E2 (20 and 100 ng) into the PO-AH region increased blood pressure and heart rate, but that of prostaglandin D2 (100 ng) had no effect. 5. The present results suggest that IL-1 beta stimulates the release of prostaglandins, presumably E series, near regions of the hypothalamus, which act on the hypothalamus to induce activation of the sympathetic nervous system. Subsequently, the blood pressure, heart rate and the plasma level of NA increase.